Exceptionally high electronic mobility in defect-rich Eu2ZnSb2−xBix alloys. Issue 12 (12th March 2020) - Chanakian, Sevan; Uhl, David; Neff, David; Drymiotis, Fivos; Park, Junsoo; Petkov, Valeri; Zevalkink, Alexandra; Bux, Sabah
Abstract : Alloying Eu2 ZnSb2 with Bi on the Sb site leads to an increase in mobility while still lowering the lattice thermal conductivity. Abstract : The Zintl compound Eu2 ZnSb2 was recently shown to have a promising thermoelectric figure of merit, zT ∼ 1 at 823 K, due to its low lattice thermal conductivity and high electronic mobility. In the current study, we show that further increases to the electronic mobility and simultaneous reductions to the lattice thermal conductivity can be achieved by isovalent alloying with Bi on the Sb site in the Eu2 ZnSb2− x Bi x series ( x = 0, 0.25, 1, 2). Upon alloying with Bi, the effective mass decreases and the mobility linearly increases, showing no signs of reduction due to alloy scattering. Analysis of the pair distribution functions obtained from synchrotron X-ray diffraction revealed significant local structural distortions caused by the half-occupied Zn site in this structure type. It is all the more surprising, therefore, to find that Eu2 ZnBi2 possesses high electronic mobility (∼100 cm 2 V −1 s −1 ) comparable to that of AM2 X2 Zintl compounds. The enormous degree of disorder in this series gives rise to exceptionally low lattice thermal conductivity, which is further reduced by Bi substitution due to the decreased speed of sound. Increasing the Bi content was also found to decrease the band gap while increasing the carrier concentration by two orders of magnitude. Applying a single parabolic band model suggests that Bi-rich compositions of Eu2 ZnSb2− x Bi x have the potential for significantly improved zT ; however, further optimization is necessary through reduction of the carrier concentration to realize high zT .